2018
DOI: 10.2215/cjn.00590118
|View full text |Cite
|
Sign up to set email alerts
|

End of Life, Withdrawal, and Palliative Care Utilization among Patients Receiving Maintenance Hemodialysis Therapy

Abstract: In this single-center study, the rate of hemodialysis withdrawals were twice the frequency previously described. Acute medical complications and frailty appeared to be driving factors. However, palliative care services were used in only a minority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 41 publications
3
55
0
2
Order By: Relevance
“…Although age would be expected to be associated with death of any etiology, including withdrawal, the strength of association of older age was greater for withdrawal relative to survival than for non‐withdrawal death relative to survival. A very recent study using patient medical records also found that older age was associated with elective withdrawal, although this study was not confined to an examination of new initiates . This suggests that the possibility of elective withdrawal in the months after dialysis initiation should be especially emphasized when counseling older patients about what the postinitiation period might hold.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although age would be expected to be associated with death of any etiology, including withdrawal, the strength of association of older age was greater for withdrawal relative to survival than for non‐withdrawal death relative to survival. A very recent study using patient medical records also found that older age was associated with elective withdrawal, although this study was not confined to an examination of new initiates . This suggests that the possibility of elective withdrawal in the months after dialysis initiation should be especially emphasized when counseling older patients about what the postinitiation period might hold.…”
Section: Discussionsupporting
confidence: 90%
“…While non‐whites (blacks and members of other racial groups) demonstrated a modest 6‐month survival advantage compared with whites, they were less than half as likely as whites to withdraw within 6 months. This finding was also concordant with the results of a recent study in which whites were much more likely to withdraw than non‐whites . As a percentage of all early deaths, withdrawal was nearly twice as frequent in whites as in blacks.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review including more than fourteen million dialysis patients of six countries identified a broad range of withdrawal between 3 per 1,000 person-years in 1966 to 49% per 1,000 person-years in 2010 [19]. More recently, in a single center study of more than 1,200 incident dialysis patients in the United States withdrawal is evaluated in up to 49% of the deaths which is twice as frequent as described previously [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are no specific data on QOL measures in patients with both advanced cancer and ESRD who are started on dialysis. Studies germane to QOL have shown that, among ESRD patients receiving dialysis in Canada, 61% regretted their decision to start dialysis . A recent study of 1226 patients in the US who were started on dialysis showed that, among the patients who died during the observation period, 49% had chosen to withdraw from dialysis .…”
Section: Eastern Cooperative Oncology Group (Ecog) Performance Statusmentioning
confidence: 99%
“…Having the palliative care service involved as part of the health care team also reinforces to patients and their family members that we will continue to care for them even if they decide not to initiate dialysis. Studies have consistently shown that the introduction of palliative care after the diagnosis of cancer improves QOL …”
Section: Eastern Cooperative Oncology Group (Ecog) Performance Statusmentioning
confidence: 99%